Production of Concentrated Red Pitaya (Hylocereus Undatus) Juice by Vacuum Evaporation (Research, Society and Development, 2023)
The processes of concentration of liquid food, especially fruit juices, are complex processes that can cause changes in physical, biochemical, and sensory properties. The main objectives of juice concentration are to increase the product's shelf life and biochemical and microbiological stability and reduce the volume, which leads to lower transport and storage costs. Processes using heat for conservation and concentration continue to be the most used by the food industry. However, heat treatments have as their main disadvantage their negative impact on the retention of nutritional and quality factors, such as colour, aroma and flavour. There are many scientific, technological, and food engineering efforts to ensure greater yield, better retention of compounds and lower processing costs. New processes and technologies have been studied for the concentration of juices. The evaporation experiments were carried out to characterize the raw material used and the final product obtained. The concentration by evaporation was carried out using a vacuum evaporator. In the industry, multi-effect evaporators are usually used to circumvent the problem of the boiling point increase caused by the solvent's partial evaporation in each effect. Therefore, since the experiments were carried out using only a single-output pump, some adaptations were necessary regarding the actual process conditions and the objectives of the evaporation experiment. The process was conducted in two stages: (1) study and industrial use of the national red pitaya; (2) concentration of the juice under vacuum and the characterization of the product obtained.